Financial Appraisal as the Basis for Development of the Efficient Corporate Financial Strategy in the Context of Economic Instability - SOBOLEVA, Yuliya Pavlovna; PARSHUTINA, Inna Grigorievna; SHAPOROVA, Olga Aleksandrovna; MARCHENKOVA, Lilia Mikhailovna; SIMONOVA, Evgeniia Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
Economic entities are faced today with the challenge of ensuring a timely flexible response to rapidly changing environmental conditions, which is connected with the development of an efficient financial development strategy. There is the growing awareness in the business community that despite the difficulties of functioning of the economy’s real sector much depends on the companies and their decisions in the field of strategic financial management. As a result, an increasingly important role is attributed to the development of methodological tools to financially appraise the performance of a company operating in an environment of economic instability, which can be applied to improve business resilience to internal and external shocks. The fundamental concepts and scientific hypotheses presented in the papers of the economic science classics, contemporary foreign and Russian scholars and specialists in the field of organizations’ strategic financial management served as theoretical and methodological basis for the study. The research methodology is based primarily on the systemic, structural, abstract and logical methods of economic analysis. General scientific methods of cognition (logical, comparative) and traditional methods of research (computational, practical, statistical, retrospective, tabular, graphic) were also used in the work. During the study, an approach to the establishment of a composite indicator has been developed and implemented, which allows to objectively appraise the financial condition of the object under study along with the methods of diagnostics that exist in the theory and practice of financial management. The authors presented an algorithm used to appraise the financial condition of an enterprise operating in the unstable environmental conditions. The applied novelty of the obtained results consists in the development of major provisions of the financial resources management strategy for a commercial enterprise operating in the conditions of uncertainty in the external and internal environment.